(untitled) (Global Journal of Management and Business Research, 2020)
Export oriented readymade garment (RMG) industry of Bangladesh has flourished at a rapid pace utilizing elastic supply of cheap female labor. But COVID-19 turns up as a new threat for this industry. As the Bangladesh Garment Manufacturers and Exporters Association (BGMEA) is one of the largest trade associations in the country representing the readymade garment industry, particularly the woven garments, knitwear and sweater sub-sectors with equal importance, it has vast responsibilities to protect the industry from massive loss. This study conducted based on current situation of supply chain in garment industry where try to find out the problem by SWOT analysis and Porter’s five forces model. After pointing out the problem this study suggests some strategies both for the during and post Covid-19 to protect garment industry from massive loss.